KAJIAN DAMPAK PENERAPAN VARIETAS KACANG HIJAU VIMA I DAN KOMPONEN TEKNOLOGI PENDUKUNGNYA DI LAHAN SAWAH - Nila Prasetiaswati; Budhi Santosa Radjit (Universitas Tribhuwana Tunggadewi, 2011)
Research was conducted in Megonten village, subdistrict Kebonagung, Demak district in 2011 which is the central area of mungbean production. The research objective was to evaluate the impact of using mungbean variety Vima I and supporting technology. Data were collected by surveys, to 20 respondents are farmers cooperator farmers who have adopted the technology research conducted in 2009. The respondent was selected by purposive sampling. The data collected was assessed by using analysis of